Trace Element Composition of the Dissolved Matter Runoff of the Russian Arctic Rivers - Alla V. Savenko; Vitaly S. Savenko (Water, 2024)
Data on the content of dissolved trace elements (P, Si, Li, Rb, Cs, Be, Sr, Ba, Mn, Fe, Co, Ni, Cu, Zn, Cd, Tl, Pb, Al, Ga, Y, Ti, Zr, Hf, Th, U, rare earth elements, F, B, Ge, V, As, Sb, Cr, Se, Mo, and W) in the river runoff from the Russian Arctic sea watersheds were systematized and generalized. There is a tendency for the decrease in the trace element concentrations in the direction from west to east for the considered Arctic watersheds (the White, Pechora, Kara, Laptev, and East Siberian seas). It was shown that the concentrations of dissolved trace elements in the river runoff from the Russian Arctic sea watersheds are in general consistent with modern estimates of the average composition of the global river runoff.